Enhancement of Resonant Converter Circuit with Output Mode Switching Capability and Wide Input Voltage Range for Battery Charging Applications - Huang, Shyh-Jier; Yeh, Tien-Yu (Conference record of the Industry Applications Conference, 2025)
This paper proposes an improved resonant converter for battery charging applications. The converter integrates a synchronous buck-boost converter and an LCL/LCCL resonant tank circuit architecture, making it suitable for a wide range of input voltage levels. The design adopts a synchronous buck-boost converter as the primary-side inverter, utilizing the transformer's magnetizing inductance as the inductor for the buck-boost converter. Since the inductor voltage of the buck-boost converter varies with the duty cycle, wide input voltage compatibility can be achieved through pulse-width modulation (PWM) control, while maintaining the advantage of a fixed operating frequency. The secondary side of this circuit adopts a switchable LCL/LCCL resonant circuit architecture. By designing the component parameters, the converter can achieve constant voltage and constant current output characteristics simply through mode-switching. In constant current mode, the secondary side employs an LCCL resonant tank for charging. In constant voltage mode, a series capacitor is added to the resonant tank, switching to an LCL resonant tank for charging. The prototype circuit constructed in this study achieves an output voltage of 90V with a variable output current ranging from 0.5A to 2A in constant voltage mode. In constant current mode, it delivers a fixed output current of 2A with an output voltage variation from 40V to 90V. Meanwhile, the zero-voltage switching is successfully achieved across a wide input voltage range. The circuit proposed in this paper provides valuable insights and references for battery charging design and applications.